THE ANALYSIS OF DISTRIBUTION CHANNEL EFFECTS ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION (STUDY CASE: PT. INDOMARCO ADI PRIMA MAKASSAR BRANCH) - Rizki Kurnia Husain; Otto Randa Payangan; Muhammad Ismail (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
Distribution problems have always been the biggest issue, especially for companies that produce their products in bulk. The wider the marketing area, the more obstacles are faced so that it is necessary to divide the marketing area in each area by placing branches or distributors. This policy pattern requires the placement of inventory at each location, and the placement of the inventory requires good handling so that inventory can be optimal, meaning that it can meet the demands of existing demand without carrying out too much storage which causes buildup in warehouses resulting in high storage costs and the possibility the occurrence of product damage is even greater. The purpose of this study is to analyze the effect of the independent variables on the dependent variable using intervening variables. The type of research used is descriptive-quantitative. This study presents the influence of distribution channels on customer loyalty through customer satisfaction. The results obtained in this study are the variable handling of goods, warehousing systems, and transportation systems directly have a significant effect on customer satisfaction PT. Indomarco Adi. The order processing variables, goods handling and warehousing systems directly have a significant effect on customer loyalty of PT. Indomarco Adi Prima. And also customer satisfaction variables directly have a significant effect on customer loyalty of PT. Indomarco Adi prima.